2022
DOI: 10.3390/medicina59010052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Self-Medication for Acne among Students of Health-Related Science Colleges at King Saud University in Riyadh Region Saudi Arabia

Abstract: Background and Objectives: In Saudi Arabia, Acne vulgaris is a very predominant ailment among adolescents, especially female university students, and self-medication has become a trend to manage this condition. To determine the prevalence of Acne vulgaris among health care students and to access the scenario of its self-medication in light of students’ knowledge, attitude, and practice towards it. Materials and Methods: This was an observational study conducted at King Saud University, Riyadh, Kingdom of Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This means people learn more through social interaction with friends/family, pharmacists and social media, as compared to books. The previous research whereas identifies the internet as one of the major sources used to gain information about selfmedication for acne (Alrabiah et al, 2023). Although the internet becomes a major source of information, still it is important to consult a professional healthcare provider to ensure the timely and proper diagnosis of acne and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This means people learn more through social interaction with friends/family, pharmacists and social media, as compared to books. The previous research whereas identifies the internet as one of the major sources used to gain information about selfmedication for acne (Alrabiah et al, 2023). Although the internet becomes a major source of information, still it is important to consult a professional healthcare provider to ensure the timely and proper diagnosis of acne and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The sample of registered CPs in Riyadh was estimated to be 2000 CPs (21). Similar to previous studies (14,(22)(23)(24)(25)(26)(27)(28) the number of samples was calculated using the Raosoft online calculator (5). To obtain a 95% confidence interval level and a 5% accepted margin of error when taking into account a 50% answer distribution, an estimated 323 participants were needed.…”
Section: Sample Sizementioning
confidence: 99%
“…Although the majority of acne cases do not require a specific medical evaluation, a medical workup may occasionally be necessary (2)(3)(4)(5). An estimated 9.4% of the global population is impacted by acne and the majority of them were being female (4)(5)(6). A more recent study in Saudi Arabia reported a prevalence of 78.5% of acne among university students (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in Saudi Arabia and other countries have highlighted instances where self-medication interactions within community pharmacies were inadequately managed ( Benrimoj et al, 2007 , Fitzpatrick and Tumlinson, 2017 , Bin Abdulhak et al, 2011 , Bawazir, 1992 , Zawahir et al, 2019 ). Furthermore, the prevalence of self-medication in Saudi Arabia has been steadily increasing ( Aljadhey et al, 2015 , Al Rasheed et al, 2016 , Al Essa et al, 2019 , Alrabiah et al, 2023 ). This current study marks the first of its kind in Saudi Arabia, aiming to explore the role of community pharmacies in mitigating the risks associated with self-medication involving doxycycline during pregnancy.…”
Section: Introductionmentioning
confidence: 99%